Research at the University of Kent and Subsequent Research Activities - Kalli, Kyriacos (My University, 2011)
The author's research activities undertaken at the Applied Optics Group, the University of Kent at Canterbury are reviewed, during his time there from 1988-1992 and 1994-1996, followed by a summary of recent research. The areas of interest are high finesse ring resonators, tunable optical filters, novel optical fiber grating sensors in glass and polymer, femtosecond laser inscription and micromachining, environmental pollution monitoring, hydrogen activated Pd films on silicon and impurity measurement on silicon wafers.
Keywords: Femtosecond lasers; Silicon; Thin films; Hydrogen; Ring Resonators femtosecond laser, pollution monitoring, thin films; silicon; Fiber gratings; Tunable Optical Filters